Negotiating Muslim Youth Identity in Southeast Asia: Psychosocial and Islamic Educational Perspectives - Alwy Ahmed Mohamed; Triono Ali Mustofa; Mahmudulhassan; Mariam Elbanna (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: This study explores the identity crisis among Southeast Asian youth shaped by political instability, cultural pluralism, modernization, and colonial legacies. It examines how Islamic ethics, psychosocial theory, and critical pedagogy can support resilient identity formation. Theoretical framework: Grounded in Erikson’s psychosocial theory, Giroux’s critical pedagogy, and Islamic concepts of selfhood (nafs), moral growth (tazkiyah), and communal belonging (ummah), this research offers a holistic lens on identity construction. Literature review: Existing studies overlook the integration of Islamic thought with Western developmental and pedagogical models in Southeast Asia. Although Islamic schools influence youth identity, their deeper psychosocial and moral roles remain underexplored in Indonesia, Malaysia, and Southern Thailand. Method: Using a qualitative, interdisciplinary approach, the study draws from ethnographic case studies, visual data, and interviews. Islamic doctrinal analysis is applied to assess faith-based coping mechanisms and moral development. Results: Identity is shown to be a dynamic, negotiated process. Islamic institutions provide moral clarity and psychological support, while the proposed Dual-Intervention Model, blending critical pedagogy with spiritual introspection, enhances youth resilience and ethical grounding. Implications: The findings inform educators and policymakers seeking to align Islamic education with psychosocial development. The model offers a culturally rooted, interdisciplinary solution to youth identity fragmentation in postcolonial contexts. Novelty: This study introduces a dual-theoretical framework that fuses Islamic ethics with psychosocial and pedagogical theory to build a context-specific approach to identity formation.